Aqueous Extract of Argania spinosa L. Fruits Ameliorates Diabetes in Streptozotocin-Induced Diabetic Rats - Hebi, Morad; Khallouki, Farid; Haidani A, EL; Eddouks, Mohamed (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2018)
Introduction: The argan tree (Argania spinosa L.) is an endemic species from south-western Morocco. Argan-based preparations have been widely used in Moroccan traditional medicine for their biological properties including diabetes especially argan oil. However, the antihypergycemic effect of the pericarp of A. spinosa fruit has never been evaluated. Objective: The purpose of this study was to investigate the effect of a single dose and daily oral administration for seven days of aqueous extract of pericarp of Argania spinosa fruit (A.E.P.F.A.S) in normal and streptozotocin (STZ) diabetic rats. Methods: The effect of A.E.P.F.A.S. (10 mg/kg) on blood glucose levels, plasma Total Cholesterol (TC) and triglyceride concentrations were measured in both normal and diabetic rats. The antioxidant capacity of the A.E.P.F.A.S was also demonstrated using test of DPPH (1-1-diphenyl 2-picryl hydrazyl). The histopathological changes in liver and pancreas have been evaluated in both normal and STZ diabetic rats. A preliminary phytochemical screening for various bioactive constituents and the antioxidant capacity were realized. Results: Single oral administration of A.E.P.F.A.S reduced blood glucose levels p 6 h after administration in STZ diabetic rats. Furthermore, blood glucose levels were decreased in STZ diabetic rats after seven days of treatment. According to the oral glucose tolerance test, the A.E.P.F.A.S. was shown to prevent significantly the increase in blood glucose levels in diabetic treated rats after glucose administration when compared to the control group. Moreover, A.E.P.F.A.S showed antioxidant activity and revealed the inhibitory concentration of 50% of free radicals (IC50) of 279.16 μg/ml. Conclusion: This study demonstrates antihyperglycemic, lowering plasma cholesterol levels and antioxidant effects of A.E.P.F.A.S. in the severe diabetic state. Further investigations are needed to elucidate the mechanism( s) of action of A.E.P.F.A.S. and the active constituent(s) of the extract.
Keywords: triglyceride